Complex refractive indices measurements of polymers in infrared bands. (September 2020) - Zhang, Xiaoning; Qiu, Jun; Zhao, Junming; Li, Xingcan; Liu, Linhua
Highlights: The complex refractive indices of PDMS with different ratios of composition in infrared bands are measured. The measured refractive indices of polymers in this paper have been compared with the calculated results by the Kramers-Kronig relations. The cause of the absorption peak of each polymer is analyzed in the paper. Abstract: Polymers are widely used in many fields such as radiative cooling, infrared stealth, optical fibers and solar cells. In this work, the complex refractive indices of seven polymers such as polydimethylsiloxane (PDMS), polymethyl methacrylate (PMMA), polycarbonate (PC), polystyrene (PS), polyethylene terephthalate (PET), polyvinyl chloride (PVC), and polyetherimide (PEI) are measured by spectroscopic ellipsometry (SE) combined with the ray tracing method (RTM) from near-infrared to mid-infrared bands (2–20 µm). The measured results of PDMS have been proved to be accurate by comparing them with previous data in the literature. The obtained refractive indices of polymers in this paper have been compared with the results calculated by the Kramers-Kronig relations. Finally, we analyze the reasons of absorption peaks of these materials in infrared bands by the vibration of chemical bonds in molecules.